Securing Private Text Messages Using a Modified ASCII-256 Caesar Cipher and Avalanche Effect Assessment - Maghfira Aida; Yulia Alfi Sinaga; Afthar Kautsar (Journal of Computers and Digital Business, 2025)
Cryptography is a scientific discipline used to protect information by transforming readable messages into forms that are unintelligible to unauthorized parties. One of the earliest and simplest cryptographic techniques is the Caesar Cipher, which remains relevant for academic exploration, particularly in understanding fundamental concepts of substitution ciphers. This study proposes a modified version of the Caesar Cipher by incorporating the full ASCII-256 character set, thereby expanding the substitution space and increasing the complexity of the encryption process. To evaluate the effectiveness of this modification, two measurement techniques were applied: the Avalanche Effect, which assesses the sensitivity of the cipher to small input changes, and the Character Error Rate (CER), which examines the accuracy and distortion level during decryption. The experimental results demonstrate that the modified cipher achieves an average Avalanche Effect exceeding 10% and a CER value above 50%, indicating enhanced resistance to simple cryptanalytic approaches and improved confidentiality of encrypted data. The implementation and simulations were performed using MATLAB R2013a to provide a controlled environment for testing and analysis. This study offers a deeper conceptual understanding of how classic ciphers can be strengthened through structural modifications and serves as a reference for introductory cryptographic research as well as educational demonstrations.